Arabic Morphological Productivity In The Translation Of Medical Terminology - Amar, Khatra (2022)
The terminology wealth of a given language indicates its development in the scientific and technical research and, hence its ability to use its linguistic potentials to be a language of science. Accordingly, the study of the morphological productivity in the translation of terminology in a given field is crucially important. The ever-increasing developments in the field of medicine in today’s world, and the English dominance in that field, made it necessary for the Arabic language to adjust itself to change by making full use of its morphological productivity potentials to create appropriate translation equivalents for English medical terms to cope with ongoing developments.